Aggregation of Gold Nanoparticles Triggered by Hydrogen Peroxide‐Initiated Chemiluminescence for Activated Tumor Theranostics. (1st October 2021) - Mao, Qiulian; Fang, Jing; Wang, Anna; Zhang, Yuqi; Cui, Chaoxiang; Ye, Shuyue; Zhao, Yan; Feng, Yali; Li, Jiachen; Shi, Haibin
Abstract: Developing endogenous photo‐activated theranostic platforms to overcome the limitation of low tissue‐penetration from external light sources is highly significant for cancer diagnosis and treatment. We report a H2 O2 ‐initiated chemiluminescence (CL)‐triggered nanoparticle aggregation strategy to activate theranostic functions of gold nanoparticles (AuNPs) for effective tumor imaging and therapy. Two types of AuNPs (tAuNP & mAuNP) were designed and fabricated by conjugating 2, 5‐diphenyltetrazole and methacrylic acid onto the surface of AuNPs, respectively. Luminol was adsorbed onto the mAuNPs to afford self‐illuminating mAuNP/Lu NPs that could produce strong CL by reaction with H2 O2 in the tumor microenvironment, which triggers significant aggregation of AuNPs resulting in enhanced accumulation and retention of AuNPs for activated photoacoustic imaging and photothermal therapy of tumors. We thus believe that this approach may offer a promising tool for effective tumor treatment. Abstract : Taking advantage of the well‐known tetrazole/alkene „photoclick" chemistry, a hydrogen peroxide (H2 O2 )‐initiated chemiluminescence‐triggered nanoparticle (NP) aggregation strategy was herein reported to activate the photoacoustic imaging and photothermal therapeutic functions of gold NPs for specific visualization and efficient treatment of tumors in vivo. This approach could provide a valuable tool for achieving precise cancer treatment.